Connecting Rheumatology Patients to Primary Care for High Blood Pressure: Specialty Clinic Protocol Improves Follow‐up and Population Blood Pressures. Issue 4 (28th March 2019) - Bartels, Christie M.; Ramly, Edmond; Johnson, Heather M.; Lauver, Diane R.; Panyard, Daniel J.; Li, Zhanhai; Sampene, Emmanuel; Lewicki, Kristin; McBride, Patrick E.
Abstract : Objective: Recognizing high blood pressure (BP) as the most prevalent cardiovascular risk factor in patients with rheumatic diseases and all adults, experts recommend clinic protocols to improve BP control. The aim of this study was to adapt and implement a specialty clinic protocol, "BP Connect, " to improve timely primary care follow‐up after high BP measurements in rheumatology clinics. Methods: We examined BP Connect in a 6‐month preimplementation and postimplementation quasi‐experimental design with 24‐month follow‐up in 3 academic rheumatology clinics. Medical assistants and nurses were trained to 1) check (re‐measuring BPs ≥140/90 mm Hg), 2) advise (linking rheumatic and cardiovascular diseases), and 3) connect (timely [<4 weeks] primary care follow‐up using protocoled electronic health record [EHR] orders). We used EHR data and multivariable logistic regression analysis to examine the primary outcome of timely primary care follow‐up for patients with in‐network primary care. Staff surveys were used to assess perceptions. Interrupted time series analysis was performed to examine sustainability and BP trends in the clinic populations. Results: Across both 4, 683 preimplementation and 689 postimplementation rheumatology visits by patients with high BP, 2, 789 (57%) encounters were eligible for in‐network primary care follow‐up. Postimplementation, the odds of timely primary care BP measurement follow‐up doubled (odds ratio 2.0, 95% confidence interval 1.4–2.9). Median time to follow‐up decreased from 71 days to 38 days. Moreover, rheumatology visits by patients with high BP decreased from 17% to 8% over 24 months, suggesting significant population‐level declines ( P < 0.01). Conclusion: Implementing the BP Connect specialty clinic protocol in rheumatology clinics improved timely follow‐up and demonstrated reduced population‐level rates of high BP. These findings highlight a timely strategy to improve BP follow‐up amid new guidelines and quality measures.